2003
DOI: 10.1039/b211163b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6H-pyrrolo[3′,4′:2,3][1,4]diazepino[6,7,1-hi]indole-8,10(7H,9H)-diones using 3-bromo-4-(indol-1-yl)maleimide scaffold

Abstract: Series of 3-arylalkyl- or 3-alkylamino-4-(indol-1-yl)maleimides and bis(indol-1-yl)maleimides were synthesised. The cyclization of the 3-substituted 4-(indol-1-yl)maleimides under the action of acids resulted in the formation of diazepine[1,4] derivatives with indoline and maleimide nuclei annelated. These compounds readily produced the corresponding indolomaleimidodiazepines[1,4] after dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 7 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…A series of derivatives of bis(indolyl)maleimides are undergoing clinical testing at present [1, 2]. Derivatives of bis(indol-1-yl)-, 2-alkylamino-3-(indol-1-yl)maleimides (for example compounds 1 and 2 ) were synthesized previously [3]. It was shown that under the action of protic acids these compounds are cyclized with the formation of a diazepine seven-membered ring with annelated indoline and maleimide fragments (3 and 4 respectively) in difference to bis(indol-3-yl)maleimides 5, which form compounds with a six-membered central ring 6 under similar conditions [4] (Scheme 1).…”
mentioning
confidence: 99%
“…A series of derivatives of bis(indolyl)maleimides are undergoing clinical testing at present [1, 2]. Derivatives of bis(indol-1-yl)-, 2-alkylamino-3-(indol-1-yl)maleimides (for example compounds 1 and 2 ) were synthesized previously [3]. It was shown that under the action of protic acids these compounds are cyclized with the formation of a diazepine seven-membered ring with annelated indoline and maleimide fragments (3 and 4 respectively) in difference to bis(indol-3-yl)maleimides 5, which form compounds with a six-membered central ring 6 under similar conditions [4] (Scheme 1).…”
mentioning
confidence: 99%
“…Another example of cyclization involving the α-methylene atom of the amino group was demonstrated by Preobrazhenskaya's group [74,75]. In the presence of strong acids, 2-(dialkylamino)-3-(indol-1-yl)maleimides 97 underwent cyclization to 1,4-diazepines 98 annelated to an indole ring [75,76].…”
Section: -100%mentioning
confidence: 99%
“…1,2 Earlier, 3,4 it was shown that intramolecular cy clizations of 3,4 bis(indol 3 yl)maleimides 1, 3 (indol 1 yl) 4 (indol 3 yl)maleimides 2, and 3,4 bis(indol 1 yl)maleimides 3 under the action of protic acids proceed differently and result in different types of compounds. 3,4 Bis(indol 3 yl)maleimides 1 under acid catalysis con ditions and after dehydrogenation form indolo [2,3]carb azole derivatives 4 (Scheme 1). In the absence of oxidant (DDQ) intermediate 5 undergoes isomerization into aminophenylcarbazole 6 (see Scheme 1).…”
mentioning
confidence: 99%
“…Research on the chemical properties and reactivity of 3,4 bisindolylmaleimides is of interest in connection with the fact that some compounds of this series and related indolo [2,3]carbazoles possess valuable biological proper ties. 1,2 Earlier, 3,4 it was shown that intramolecular cy clizations of 3,4 bis(indol 3 yl)maleimides 1, 3 (indol 1 yl) 4 (indol 3 yl)maleimides 2, and 3,4 bis(indol 1 yl)maleimides 3 under the action of protic acids proceed differently and result in different types of compounds.…”
mentioning
confidence: 99%